Improving students’ activeness and critical thinking skills through problem based learning - Fitriani Fitriani; Nurhuda Nurhuda; Ade In Ina (Journal of Science and Education (JSE), 2021)
This research is aimed to increase the activeness and critical thinking skills of students by applying the problem based learning model. The type of research is classroom action research. The research was conducted at the Accounting Education Study Program, Faculty of Teacher Training and Education, Islamic University of Riau. The research subjects were 1st semester students, who took the Introduction to Management course for the 2020/2021 academic year. The data in this study were obtained from observation sheets and test instruments. The data analysis technique used descriptive analysis for aspects of activeness and critical thinking skills. The results showed that the average of students’ activeness in the first cycle reached 74.5% (fair category) and in the second cycle students' activeness reached 86% with good category. Then, students’ critical thinking in the first cycle reached 77% in the Fair category, and in the second cycle it gained 86% in the good category. Therefore, there is an increase in students’ activeness and critical thinking skills by applying the problem based learning model. Based on the research findings, the researcher would like to propose the following suggestions namely: 1) Making the students more motivated during online learning by using problem-based learning, 2) Appreciating the students’ ideas to make them more confident, 3) The research was only composed of two cycles, so that the next researchers can carry out more than two cycles to maximize student’s activeness and critical thinking. This study also still has limitations, namely, the questions used are only in the form of essay questions and have not used varied question instruments.